Impact of competition and regulation on prices of mobile services: Evidence from France - Lukasz Grzybowski; Ambre Nicolle; Christine Zulehner (International Telecommunications Society (ITS), 2017)
In this paper, we assess the impact of competition and regulation on prices of mobile services in France. We estimate hedonic price regressions using data on tariff plans offered by the main mobile telecommunications operator in France between May 2011 and December 2014. In this time period, the obtained quality-adjusted price index decreased by about 51% as compared to a decline in average prices without quality adjustment of 8.9%. In a second step, we relate the quality-adjusted prices to a set of competition and regulation variables and find that the launch of 4G networks by mobile operators was the main driver of price reductions for classic tariffs with commitment. Low cost tariffs without commitment which were introduced to pre-empt the entry of low cost competitor declined at the time of entry. Moreover, we find that regulation, which is approximated by the level of mobile termination charges and international roaming price caps for voice and data, has jointly a significant impact on quality-adjusted prices. In percentage terms, competition is responsible for about 68% of total price decline. We conclude that the reduction in quality-adjusted prices in the last years was largely caused by competition between established operators and by entry of fourth low cost operator.
Keywords: L13; L50; L96; 330; Mobile telecommunications; hedonic price regression; regulation; entry